Parents’ Perspectives on the Costs of education - Murni, Arie Widya; Suryanti, Suryanti; Wiryanto, Wiryanto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
The research aims to describe the views of parents on the high cost of education. This research uses a descriptive method with a qualitative approach. Data were collected using structured interview guidelines. The research informants were the guardians of students in the Sidoarjo District area, totaling 60 people according to the data requirements needed by the researchers. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results showed that the parents in choosing a school considered the facilities, curriculum, service, and quality factors of a school. The high cost of education is not a barrier for parents to continue their child's education because if a child excels and has a strong will, there will always be a way to continue his education to a higher level.